2022
DOI: 10.1093/nsr/nwac074
|View full text |Cite
|
Sign up to set email alerts
|

Indian plate paleogeography, subduction and horizontal underthrusting below Tibet: paradoxes, controversies and opportunities

Abstract: The India-Asia collision zone is the archetype to calibrate geological responses of continent-continent collision, but hosts a paradox: there is no orogen-wide geological record of oceanic subduction after initial collision around 60-55 Ma, yet thousands of kilometers of post-collisional subduction occurred before arrival of unsubductable continental lithosphere that currently horizontally underlies Tibet. Kinematically restoring incipient horizontal underthrusting accurately predicts geologically estimated di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 105 publications
(301 reference statements)
3
10
0
Order By: Relevance
“…The reversal of 'sedimentary polarity' from cratonic sources to orogenic belt and cratonward migration of a flexural forebulge in foreland basin systems are common, both in collisional (Himalaya-type) (DeCelles et al, 2014;Ding et al, 2009) and retroarc (Andean-type) systems (Horton, 2018, 2022 andreferences therein). Finally, we agree with the statement that either significant Cenozoic crustal shortening within Asia and the Himalaya or one or more Cenozoic suture zones has not been identified (Kapp & DeCelles, 2019), and those disputes will continue until we confidently find the 'missing' Indian continental crust or new oceanic crustal remnants within the Himalayan orogen or southern margin of the Asian continent (Ding et al, 2022;Kapp & DeCelles, 2019;Parsons et al, 2020;van Hinsbergen, 2022). We appreciate the assistances from Weilin Zhang, Tao Zhang, Dawen Zhang, Fuli Wu and Dhan Bahadur Khatri in the field and Xiaoli Yan and Wanfeng Chen in the laboratory.…”
Section: India-asia Collisionsupporting
confidence: 64%
See 2 more Smart Citations
“…The reversal of 'sedimentary polarity' from cratonic sources to orogenic belt and cratonward migration of a flexural forebulge in foreland basin systems are common, both in collisional (Himalaya-type) (DeCelles et al, 2014;Ding et al, 2009) and retroarc (Andean-type) systems (Horton, 2018, 2022 andreferences therein). Finally, we agree with the statement that either significant Cenozoic crustal shortening within Asia and the Himalaya or one or more Cenozoic suture zones has not been identified (Kapp & DeCelles, 2019), and those disputes will continue until we confidently find the 'missing' Indian continental crust or new oceanic crustal remnants within the Himalayan orogen or southern margin of the Asian continent (Ding et al, 2022;Kapp & DeCelles, 2019;Parsons et al, 2020;van Hinsbergen, 2022). We appreciate the assistances from Weilin Zhang, Tao Zhang, Dawen Zhang, Fuli Wu and Dhan Bahadur Khatri in the field and Xiaoli Yan and Wanfeng Chen in the laboratory.…”
Section: India-asia Collisionsupporting
confidence: 64%
“…Parsons et al (2020) and van Hinsbergen (2022) compared the abovementioned collision models associated with their strengths and weaknesses and pointed out that none of the present models for the India‐Asia collision are entirely satisfactory with current provenance constraints, palaeomagnetic datasets and magmatic records at the same time. It is worth noting that the current palaeomagnetic datasets concerning the India‐Asia collision are controversial, and each collision model has supportive palaeomagnetic datasets.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, the Himalayas have become a typical area for studying orogeny and metallogenic processes (Cao, Pei, et al, 2022). Although considerable research has been performed in the Himalayas in the past (van Hinsbergen, 2022; Yin, 2006), new geological evidence and the development of new analytical techniques in recent years have substantially clarified the geological evolutionary process of the Himalayas and many new ideas have been proposed. For example, (1) in terms of tectonic evolution, palaeomagnetic evidence suggests that there was a “Great India Basin” on the northern margin of the Indian continent during the Cretaceous period, which led to two collisions between the India and Lhasa blocks (van Hinsbergen et al, 2012) circa 58 Ma and 25–15 Ma (van Hinsbergen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The mantle below India and the Indian Ocean was among the first regions where deep mantle structure was correlated to subduction history (Hafkenscheid et al, 2006;Replumaz et al, 2004;van der Voo et al, 1999). These studies identified multiple detached slabs, and the shallowest of these are identified hundreds to more than 1,500 km to the south of the modern northern extent of the Indian continental lithosphere which is imaged sub-horizontally below Tibet over a distance of 300-800 km north of the modern plate boundary, the southern Himalayan front (Agius & Lebedev, 2013;Chen et al, 2017;van Hinsbergen, 2022;van Hinsbergen et al, 2019) (Figure 2). Clearly, these geodynamic constraints differ completely from those used for the past numerical models simulating slab detachment and from which the currently perceived diagnostic geological signatures of slab detachment are derived.…”
mentioning
confidence: 99%